Constitutive models for rubber VII : proceedings of the 7th European Conference on Constitutive Models for Rubber, ECCMR, Dublin, Ireland, 23 September 2011 /: proceedings of the 7th European Conference on Constitutive Models for Rubber, ECCMR, Dublin, Ireland, 23 September 2011. (©2012) - Unknown
No abstract available